Public-Private Partnerships : Reference Guide Version 1.0 - World Bank Institute; PPIAF (World Bank, Washington, DC, 2013)
The Public-Private Partnerships (PPP) reference guide seeks to provide advice on what PPP practitioners should know, rather than provide advice on what to do. The guide sets out the main topics, looks at the key issues that must be addressed, and provides what we consider the most important references that PPP practitioners can turn to for answers and to enhance their own knowledge and understanding. It is structured into separate sections that focus on three main areas, firstly what are PPPs, when might they be used and the advantages and disadvantages relative to public provision; secondly the policy, legal and institutional frameworks that should be put into place to help improve their effectiveness; and finally the ways in which PPP projects can be developed and implemented. A diverse range of case studies and institutional solutions, from all parts of the world, are presented in the PPP reference guide.